SURVEI NEED ASSESSMENT BIMBINGAN TEKNIS TENAGA PERPUSTAKAAN TAHUN 2020 DI INDONESIA - Kamilah Kinanti, S.Hum; Isti Sulastari, S.Hum (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2022)
Bimbingan Teknis Tenaga Perpustakaan (Bimtek), literally translated as Technical Training for Library Technician, is an activity carried out by the National Library of Indonesia through the Librarian Development Center (P3) unit as an effort to fulfill their responsibilities as a supervisory board. With a target of thousands of participants from all provinces in Indonesia, The Bimtek spent a lot of energy and cost, therefore it would be fruitless when the implementation was far from the target. To avoid this, organizers need to finalize the planning as best as possible, one of which is by assessing the need for Bimtek materials that are in accordance with the interests and needs of the participants. Through this research, the authors conducted a need assessment for the first time at the P3 unit Bimtek involving librarians and library technicians on a national scale.. The research was conducted using a descriptive quantitative approach and survey method of 2.080 Library Technician respondents in Indonesia, the questionnaire was built by adopting the Indonesian National Work Competency Standards in the field of Libraries. The results show that the most chosen Key Functions by the respondents is Library Information and Communication Technology.